Path Planning for Parking of Four Wheeled Vehicle with Minimum Energy and Optimum Parking Space - Lutfan Milzam, Ahmad; Usman, Tarmizi; Ikhwan, Muhammad; Mahmudi, Mahmudi; Amri, Saiful (Transcendent Journal of Mathematics and Applications, 2022)
As the number of private vehicles grows, so does the demand for parking space. It was also in charge of traffic congestion and high parking fees in downtown, particularly near public services and the central business district. The goal of this paper was to optimize path planning with the least amount of energy and the most parking space. To achieve this goal, three parts of optimization were used. They were divided into three categories: optimal parking space for obtaining area bounded and parking angle, path planning with boundaries and constraints to find the path with the least amount of energy, and finally vehicle direction for comparison with other recent works. The simulation revealed that the best parking space could result in a parking angle as the final vehicle direction. Based on the results, the produced path was more efficient, with an objective function energy of 394.44 unit of energy and a vehicle speed of 4.3 km/h. Because of its closeness to previous work, the route verified that it could be driven in reverse parking action.